2010
DOI: 10.1007/s10494-010-9315-y
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds Number Effects on the Coherent Dynamics of the Turbulent Horseshoe Vortex System

Abstract: The adverse pressure gradient induced by a surface-mounted obstacle in a turbulent boundary layer causes the approaching flow to separate and form a dynamically rich horseshoe vortex system (HSV) in the junction of the obstacle with the wall. The Reynolds number of the flow (Re) is one of the important parameters that control the rich coherent dynamics of the vortex, which are known to give rise to low-frequency, bimodal fluctuations of the velocity field (Devenport and Simpson, J Fluid Mech 210: 23-55, 1990; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 34 publications
(141 reference statements)
10
64
0
Order By: Relevance
“…Also, the slopes of the radial profiles (Figure 9) within the wake region are becoming flatter towards the wake region. According to the literature, the flow components that drive the temporal evolution and the shape of the wake region are the vortices that are shed periodically downstream of the pier [4,40] and the oscillating legs of the horseshoe vortex [28,29,40]. Similar to the observations at the front and the side regions, there is not an evident imprint of the aforementioned flow components in the scour rate maps.…”
Section: Interpretation Of the Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Also, the slopes of the radial profiles (Figure 9) within the wake region are becoming flatter towards the wake region. According to the literature, the flow components that drive the temporal evolution and the shape of the wake region are the vortices that are shed periodically downstream of the pier [4,40] and the oscillating legs of the horseshoe vortex [28,29,40]. Similar to the observations at the front and the side regions, there is not an evident imprint of the aforementioned flow components in the scour rate maps.…”
Section: Interpretation Of the Resultsmentioning
confidence: 55%
“…The reduced scour rates, at the front and side regions, are commonly explained by the increase in the size of the horseshoe vortex that scales with the span of the scour hole [13,28,29]. As the size of the horseshoe vortex increases, its strength decreases and exerts lower shear stresses on the bed.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies employing the state-of-the-art in physical and numerical modelling (Praisner & Smith 2006b;Paik, Escauriaza & Sotiropoulos 2007;Kirkil & Constantinescu 2009;Sabatino & Smith 2009;Escauriaza & Sotiropoulos 2011c) showed that the time-averaged horseshoe vortex system consists of: (i) a primary vortex (HV1), which rotates in a clockwise sense (assuming that flow enters the junction region from the left), (ii) a secondary vortex (HV2) again with a clockwise sense of rotation and located upstream of HV1 and (iii) a corner vortex (CV) of counterclockwise rotation positioned downstream of HV1. A tertiary vortex (HV3) is frequently resolved in instantaneous topologies and is located at the saddle between HV1 and HV2 (Praisner & Smith 2006a;Gand et al 2010;Escauriaza & Sotiropoulos 2011c). Occasionally, the cinematography of the flow field reveals various smaller and short-lived vortical structures upstream of HV2.…”
Section: Junction Flow Dynamicsmentioning
confidence: 99%
“…Occasionally, the cinematography of the flow field reveals various smaller and short-lived vortical structures upstream of HV2. However, the dependence of the dynamics of the instantaneous junction vortices, including their number, on Re D remains unclear (Dargahi 1989;Escauriaza & Sotiropoulos 2011c).…”
Section: Junction Flow Dynamicsmentioning
confidence: 99%